Using solicited diaries for longitudinal evaluation of the different perceptions on consumption among youth (Olhar de Professor, 2011)
Aiming to contribute to the development of new research techniques within qualitative research methodology, this article discusses the use of solicited diaries and its applicability as a technique that describes, constructs narratives and promotes self-reflection of the research participants about consumption. In order to collect data on the habits and perceptions about consumption among youth, high school students of the 9th grade used the tool during nine days. The article discusses the process of selectiong the participants, conducting a pilot study and applying the solicited diaries and complementary techniques, such as exhibition of videos, debates and application of questionnaires to collect qualitative and quantitative data. The results provided a longitudinal evaluation of students’ consumption habits and allowed the construction of units of analysis and categories in terms of consumption perceptions. It was concluded that solicited diary is a valuable data collection tool, particularly with respect to learning about everyday experiences. Furthermore, the tool produces rich descriptions, narratives and reflections that allow self-knowledge of the participants and therefore are a didactic resource for individual and collective teaching-learning activities when coordinated through a group discussion.
Keywords: Qualitative research methodology. Solicited diaries. Consumption. Education.